An evaluation of sovereign-backed securities (SBSs): Potentials, risks and political relevance for EMU reform - Markus Demary; Jürgen Matthes (Institut der deutschen Wirtschaft (IW), 2017)
The EU Commission proposes establishing Sovereign-Backed Securities (SBSs) as a class of safe assets for the euro area. SBSs are generated by an issuing agency that would purchase a large diversified portfolio of national sovereign bonds, and finance the purchases by issuing (at least) two types of structured bonds: a risk-free senior SBSs tranche and a risky junior SBSs tranche. Overall, we recognise that the SBSs concept has the theoretical potential to improve financial stability and financial integration in the euro area, provided it is built on a sound framework that overcomes several potential technical and political problems. However, SBSs could pose the risk of eventually leading to unconditional debt mutualisation in times of severe crisis. With regard to technical problems, it is not clear whether the SBSs concept represents a viable business model for a private entity, and whether senior and junior SBSs would find sufficient demand, particularly in times of crisis. If the market for the junior tranche broke down, the whole concept would collapse. In such instances, the political risk could arise that rescue measures are taken that, in contrast to existing rescue mechanisms (ESM and OMT), are not subject to sufficient controls by Member States, solvency tests and reform requirements (conditionality). Another political risk relates to the introduction of the SBSs concept, which is regarded here as one part of a political compromise. We foresee the danger that the second part - de-privileging national sovereign bonds in banking regulation to sever the sovereign-banking nexus - may not be followed through, due to political resistance and to sequencing problems with introducing SBSs. Other political problems concern possible market distortions even in non-crisis times (particularly in primary markets), and the potential irreversibility of the concept. [...]
Keywords: 330; Staatspapier; Risiko; Eurozone